Born global: antecedents and consequences of innovation capabilities - Malodia, Suresh; Dhir, Amandeep; Alshibani, Safiya Mukhtar; Christofi, Michael (My University, 2023)
Innovation capabilities are considered a key factor impacting the success and sustainability of born global firms across the world. These capabilities are even more significant for the born global firms from emerging markets. In this study, we propose an overarching conceptual framework called ICONIC to explain the factors that are critical for developing innovation capabilities in born global firms. Using grounded theory with a triangulation approach, we define innovation capabilities as a multi-dimensional construct with three sub-dimensions: business model innovation, improvisation abilities, and personalized problem-solving. Furthermore, we identify three antecedents (firm-related factors, competition-related factors, and customer orientation) leading to innovation capabilities and discuss the tangible and intangible outcomes of innovation capabilities. In this study, we also propose a set of propositions describing the nature of the relationship between different constructs in our framework. Finally, we discuss the theoretical contributions and implications for born global firms and policymakers to realize the strategic goals of internationalization.
Keywords: Born global; Innovation; Innovation capabilities; Internationalization